GE_GERICHTE P/10325/2013 vom 6. Februar 2015 - GE Cour de justice (2015)
ABUS DE CONFIANCE; VOL(DROIT PÉNAL); DESSEIN D'ENRICHISSEMENT; APPROPRIATION ILLÉGITIME; INDEMNITÉ(EN GÉNÉRAL); PLAIGNANT; FRAIS DE LA PROCÉDURE | CP.138.1.1; CP.139.1